Degraded and upgraded? Economic activity in a diversifying inner-city subarea - Korcelli-Olejniczak, Ewa (Argomenti, 2017)
The paper analyses the relations between economic performance, social diversification and overall systemic transformation in a socially deprived, but dynamic subarea of Warsaw – Praga Północ. ‘Old Praga’ is treated here as a specific laboratory of contemporary urban change. Actually, its pre-war tradition of multiculturalism and the transformation into ‘historic slums’ under socialism imprinted on its memory clash with a recent socio-economic diversification, that is generated by an early-stage gentrification, and also by the inflow of ethnic minorities. Keywords: degradation, entrepreneurship, diversity, gentrification, Warsaw.